REPRESENTASI PEREMPUAN DALAM MAJALAH AYAH BUNDA - Astuti, Sri Puji (Faculty of Humanities, Diponegoro University, 2015)
Ayah Bunda Magazine is a magazine aimed at women and men who already have a child and married but have not obtained offspring. Nevertheless, this paper contains more issues related to women. Therefore, in this magazine allegedly many use the term that represents women. How the representation of women in the Ayah Bunda magazineÂ which is discussed in this paper is. Method of collecting data which was used in this study was the scrutinizing method followed by technique noted. Discourse analysis used content analysis. Based on the results of the study was found that women's representation in the Ayah BundaÂ magazine Â shown with a term that refers to the female nature wasteful, less logical, anxious. The appearance should be interesting, limited to the motion, like a complicated thing, and prioritize domestic interests.